2012
DOI: 10.5194/amt-5-1173-2012
|View full text |Cite
|
Sign up to set email alerts
|

CRISTA-NF measurements with unprecedented vertical resolution during the RECONCILE aircraft campaign

Abstract: Abstract. The Cryogenic Infrared Spectrometers and Telescope for the Atmosphere -New Frontiers (CRISTA-NF), an airborne infrared limb-sounder, was operated aboard the high-flying Russian research aircraft M55-Geophysica during the Arctic RECONCILE campaign from January to March 2010. This paper describes the calibration process of the instrument and the retrieval algorithm employed and then proceeds to present retrieved trace gas volume mixing ratio cross-sections for one specific flight in this campaign. We a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 46 publications
1
65
0
Order By: Relevance
“…Linearly derived precision and accuracy figures for the discussed species are given in Table 1; comparisons with measurements by other in situ and remote sensing instruments has ascertained the validity of these figures for a different research flight (see Ungermann et al, 2012). The vertical resolution is shown for an exemplary profile in Fig.…”
Section: Filamentary Structure In Observed Trace Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Linearly derived precision and accuracy figures for the discussed species are given in Table 1; comparisons with measurements by other in situ and remote sensing instruments has ascertained the validity of these figures for a different research flight (see Ungermann et al, 2012). The vertical resolution is shown for an exemplary profile in Fig.…”
Section: Filamentary Structure In Observed Trace Gasesmentioning
confidence: 99%
“…A detailed description of the first retrieval of this set of measurements is given by Weigel et al (2012). Ungermann et al (2012) improved this setup by employing a more accurate line-of-sight determination and a finer retrieval grid. In addition, horizontal regularisation was added to lower the impact of stochastic error sources on the results (see Ungermann, 2013).…”
Section: Appendix a Retrievalmentioning
confidence: 99%
“…The Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA) instrument continues the heritage of the series of MIPAS (Michelson Interferometer for Passive Atmospheric Sounding; Fischer and Oelhaf, 1996;Piesch et al, 1996;Friedl-Vallon et al, 2004) and CRISTA (CRyogenic Infrared Spectrometers and Telescopes for the Atmosphere; Offermann et al, 1999;Ungermann et al, 2012) instruments. One major improvement of GLORIA compared to its limb-scanning precursors is the usage of an imaging array detector for significantly higher spatial sampling and precise relative pointing.…”
Section: S Johansson Et Al: Gloria Measurement Characterization Andmentioning
confidence: 99%
“…Observations of MIPAS aboard Envisat (Fischer et al, 2008, and references therein) were utilized to study the chemical composition from tropospheric to mesospheric altitudes. Airborne observations by MIPAS-STR (e.g., Piesch et al, 1996;Woiwode et al, 2012, and references therein) and CRISTA-NF (e.g., Ungermann et al, 2012) showed that middle infrared observations allow the resolution of narrow vertical structures in trace gas distributions along flight track with high accuracy under cloud-free conditions. The next generation of infrared limb sounders involves imaging detectors, and the airborne prototype instrument GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) successfully demonstrated the capabilities of this new detection technique (Friedl-Vallon et al, 2014;Riese et al, 2014).…”
Section: Infrared Observationsmentioning
confidence: 99%